Adaptive and functional polymers, textiles and their applications - Hu, Jinlian (Imperial College Press ; Distributed by World Scientific, 2011)
Adaptive polymers include those which are responsive to different stimuli - namely physical, mechanical, chemical and biological - with controlled and/or predicable behavior. Many technological breakthroughs and scientific advances have been made in the last few decades and this volume aims to cover the most up-to-date studies and achievements in some adaptive polymers, in terms of principles of adaptiveness, properties, structure design and characterization with an emphasis on their applications, particularly in textiles, skin care, medicine and other related areas. Some versatile functional polymers, such as Chitosan, cylodextrin and dendrimer, and hyper-branched polymers are also introduced in order to provide a source for people in different professions when searching for knowledge and inspiration in the field of adaptive and functional polymers. This book is multi-disciplinary in nature as well as accessible to a wide variety of readers.